A multi-layered computational model for wrinkling of human skin predicts aging effects. (March 2020) - Zhao, Y.; Feng, B.; Lee, J.; Lu, N.; Pierce, D.M.
Abstract: The development and progression of wrinkles from young to aged human skin relates to both structural and mechanical changes induced by aging. Here we aim to better understand the interaction of skin's layered morphology with dynamic wrinkles predicted in young and aged skin. First, we compare the predictions of wrinkling from 3-D finite element models of human skin including two to six distinct and anatomically motivated layers. Second, we perform parametric analyses using our six-layered model to determine how age-related changes in the architecture of human skin affect dynamic surface wrinkling. Specifically, we consider the following aging-related changes in the morphology of skin: flattening of the dermal-epidermal junction (DEJ) interface; thinning of both the viable epidermis (VE) and the reticular dermis (RD); and thickening of the papillary dermis (PD). We use skin compression to model dynamic, expressional wrinkles due to muscle contraction, and volumetric tissue loss to model effects of aging in wrinkling simulations. Our results highlight the role of skin's multi-layered structure in the modeling of wrinkling formation. Our six-layered model, consisting of all of the mechanical layers, predicts deep wrinkles with better fidelity than models including fewer layers. From our parametric study, applying our six-layered model, we conclude that: (1) the relative thicknesses of the layers in the epidermis or dermis significantly influences surface wrinkling in skin; and, (2) flattening of the DEJ with aging enhances surface wrinkling. Thinning of VE increases the relative stiffness of the epidermis and thus enhances dynamic wrinkling, while thickening of PD or thinning of RD has the same effect by reducing the equivalent stiffness of the substrate. Consequently, strategies to minimize wrinkling could maintain the undulating morphology of the DEJ, thereby delaying dynamic wrinkling and delaying the propagation of buckling into the deeper dermis or hypodermis. Additional strategies to minimize wrinkling could target preventing the VE and RD from thinning or preventing the PD from thickening. Graphical abstract: Image 1 Highlights: Compare predictions of wrinkling from models of skin with two to six distinct layers. Determine how age-related changes in human skin affect dynamic surface wrinkling. Conclude that flattening of the dermal-epidermal junction in aging enhances wrinkling. Our six-layered model has advantages in probing the formation of large, deep wrinkles. Simulation results agree well with histological images from forehead wrinkles.